1D SEISMIC VELOCITY MODEL DETERMINATION AND HYPOCENTER RELOCATION USING WAVEFORM CROSS-CORRELATION DATA AROUND CENTRAL AND EAST JAVA REGION - Muttaqy, Fa'iz
Java Island is highly active tectonic zone and also has a complex geological system as a result of the Indo-Australian plate that subducted under the Eurasian plate. This complexity produces many large and destructive earthquakes. Moreover, Java is the most densely populated region in Indonesia. The investigation related to the seismicity that brings the subsurface information needs to be done to improve the understanding of earthquake source mechanism and the impact on the potential hazard in the study area. In this study, we would like to determine 1D velocity model and hypocenter relocation with waveform cross-correlation data by using hypocenter distribution based on observed arrival times of P and S-wave, and also 34 seismometers of BMKG network that distributed along Central and East Java. There are 1,529 selected events that fulfilled the criteria, they have a magnitude (Mw) > 3, and a clear onset P and S arrival. As the quality control of observed data, all of the phases were plotted onto the Wadati diagram and Vp/Vs ratio is 1.75. Based on the relocation result by using updated 1D velocity model and cross-correlation data, it showed a better performance in determining the hypocenter location than before relocation, also, it represents the geological features that may exist around the study area. This statement is proved by visually comparing the hypocenter distribution and statistically. The events applied by non-linear method were distributed more clustered in several areas, and also correlated with geological structure and historical earthquakes in the study area. Based on the hypocenter relocation result, seismicity around Central and East Java were distributed in the southern part of the island, such as in the south of Kebumen, Yogyakarta, Pacitan, Malang and Banyuwangi as consequences of subduction activity. Moreover, the event clusters in the shallow depth were probably controlled by the activity of inland faults such as Opak, Kendeng, and Rembang-Madura-Kangean-Sakala Fault. As the further plans, this study will be expanded to performing seismic tomography imaging beneath Central and East Java region